Tolerability and Efficacy of a Medical Device Repairing Emollient Cream in Children and Adults with Mild to Moderate Atopic Dermatitis - Andreas Pinter; Marie-Dominique Thouvenin; Adeline Bacquey; Ana Beatris Rossi; Thérèse Nocera (Adis, Springer Healthcare, 2019)
Abstract Introduction Regular emollient application is recommended for managing atopic dermatitis (AD). Although many emollients are available, only AD-tested medical device repairing emollient creams (MDRECs) can be recommended for treating and preventing AD skin lesions. Here, we evaluated the tolerability and benefit of a new MDREC in an open-label study in infants, young children, and adults with mild to moderate AD. Methods Subjects (or their parents or guardians) were instructed to apply the MDREC to AD lesions or areas of dry skin twice daily for 3 weeks. Investigators assessed tolerability and AD severity at days 1, 8, and 22. Subjects assessed AD severity weekly, recorded any adverse events, and reported their satisfaction with the MDREC at day 22. Results Sixty-one subjects (19 infants, 22 children, and 20 adults) were included and 59 completed the study. At inclusion, 49% of the infants and young children and 15% of the adults were experiencing flares of AD. At day 22, the local tolerability of the MDREC was judged by the investigators as excellent in all the children and in 18 of the 20 adult subjects (90%). All adverse events were mild and transient. Investigator- and subject-assessed AD severity progressively decreased at each assessment for each age subgroup. Conclusion This study shows that the MDREC was well tolerated when applied to AD skin lesions in infants, young children, and adults and suggests this product can be used daily to control the signs and symptoms of AD. Funding Laboratoires Dermatologiques Ducray, Pierre Fabre Dermo-Cosmétique.